2019
DOI: 10.1111/inm.12686
|View full text |Cite
|
Sign up to set email alerts
|

Living with bipolar disorder in Chile: A qualitative study

Abstract: Bipolar disorder (BD) is an important factor contributing to rates of higher morbidity and mortality with serious consequences on the quality of life. There is limited literature on life experience of people living with BD in Chile. For this reason, this study examines the life experiences of Chilean clients with BD. Semi-structured interviews were conducted, and clients aged 40-65 years, euthymic, with a preserved judgement of reality were included. A thematic analysis was conducted, and two themes and subthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Next, another result shows that avoidant coping strategies can directly impact quality of life and, at the same time, partially influence it via self-stigma. There is a reciprocal causal relationship between avoidance and self-stigma, forming a vicious cycle ( 59 , 60 ). Cavelti et al.’s study also demonstrated that lower scores on avoidance are associated with lower self-stigma and higher quality of life ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Next, another result shows that avoidant coping strategies can directly impact quality of life and, at the same time, partially influence it via self-stigma. There is a reciprocal causal relationship between avoidance and self-stigma, forming a vicious cycle ( 59 , 60 ). Cavelti et al.’s study also demonstrated that lower scores on avoidance are associated with lower self-stigma and higher quality of life ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a social discourse that demands respect for differences has emerged. However, prejudices toward MDs are still present, associating them with danger (Grandon et al, 2018), especially in diagnoses such as schizophrenia, minimizing the opinion of those affected on matters of their interest (Grandon et al, 2021), and, generally, limiting their opportunities (Hormazabal‐Salgado & Poblete‐Troncoso, 2020).…”
Section: Introductionmentioning
confidence: 99%